Analysis of User Satisfaction Factors for the FOTOYU Application using EUCS Method - Revi Amelia Dwifa Futri; Apriansyah Putra; Ari Wedhasmara; Mira Afrina (SISTEMASI, 2026)
The increasing adoption of digital technologies, particularly those powered by Artificial Intelligence (AI), has accelerated the development of applications aimed at improving service quality and user experience, one of which is the FotoYu application. This study aims to evaluate user satisfaction with the FotoYu application using the End-User Computing Satisfaction (EUCS) model, which comprises five dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. A quantitative research approach was employed using a survey method, with questionnaires distributed to 145 FotoYu users selected through purposive sampling. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that all measurement indicators satisfied the required validity and reliability criteria, confirming that the research instrument was appropriate for assessing user satisfaction. The structural model evaluation produced an adjusted R² value of 0.784, indicating that the five EUCS dimensions collectively explained 78.4% of the variance in user satisfaction, while the remaining 21.6% was attributable to factors outside the proposed research model. Furthermore, the effect size (f²) analysis revealed that Content had the strongest influence on user satisfaction, followed by Ease of Use, Format, Timeliness, and Accuracy. These findings demonstrate that the EUCS model is an effective approach for evaluating user satisfaction with the FotoYu application while providing valuable insights to support service quality improvement and enhance the overall user experience.